Eco-Physiological Responses of Native Desert Plant Species to Drought and Nutritional Levels: Case of Kuwait - Madouh, Tareq A. (Frontiers in Environmental Science, 2022)
Drought is the most critical limiting factor affecting plant survival, development and adaptation in the desert ecosystem. Native desert plant species are adaptable natural biomass crops of the desert’s ecosystem. These native species use water efficiently and tolerate drought and other environmental constraints. In addition, they sustain moderate nutritional values that are essential in terms of maintaining optimum vegetation development and productivity, and tolerating natural grazing. The objective of this study was to quantify the biomass production and nutritive values of three native desert grass species as influenced by drought stress i.e. 100%, 75%, 50% and 25% potential evapotranspiration (ETp). Three native desert grasses viz. Cenchrus ciliaris, Lasiurus scindicus, and Pennisetum divisum, were grown in pots, irrigated with fresh water in a greenhouse and investigated for their drought tolerance and nutritive values. The results showed that the grasses differ in their responses to drought stress by controlling stomata conductance (gs). The gs increased significantly (P<0.001) with adequate irrigation (100% and 75% ETp) and decreased with 50% and 25% ETp in all species. Under moderate drought stress (75 and 50% ETp), all desert grasses used the water efficiently and produced a considerable dry matter yield and stable amounts of nutritive value. At 50% ETp all desert species showed a significant increase (P<0.001) in root biomass than shoots that increased water absorption to survive a drought environment. The L. scindicus, exhibited a significantly higher increase (P<0.001) in root formation at 25% ETp compared to the 100% ETp treatment. In all the grass species, the protein contents increased as drought stress increased. No significant differences in fat content were detected under all irrigation conditions, while, the ash content was significantly (P<0.001) influenced by severe drought stress. Under natural desert conditions, these adjustments may reduce transpiration demand relative to water deprivation leading to improved species establishment and supported adaptation to severe desert environments. Understanding the physiological responses and the requirements of desert plant species can be excellent way to restore ecological functions and biodiversity conservation in a desert environment.